Growth and Survival Rate of Maanvis Fish (Pterophyllum scalare) With Different Feed Combinations - Indri Ika Cahyani; Usman M Tang; Mulyadi Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis study aims to determine the combination of natural food with the best artificial feed for growth and survival of maanvis fish (Pterophyllumscalare). The method of this research was using the experimental method with Completely Randomized Design (CRD) by using one factor of 5 treatment levels and 3 replications. The combination of feed in treatment is: 1: 100% Tubifexsp, 2: 75% Tubifex sp. + 25% pellets, 3: 50% Tubifex sp. + 50% pellets, 4: 25% Tubifex sp. + 75% pellets, and 5: 100% pellets. The fry size was around 2-4 cm and weight was 1,32 g then reared in the aquarium by 10 L of water and 10 fishes of stocking density each aquarium. The fish were reared for 40 days and feed is given as much as 10% of biomass weight, e times a day of feeding frequency.Parameters observed included absolute length and weight growth, specific growth rates, survival rates and water quality. The results showed that the best treatment was 100% Tubifexsp by giving absolute weight growth for 1,76 g, absolute longevity for 2,06 cm, specific growth rate for 1.91% and fish survival for 98%. The conclusion is different types of natural diets significantly affect the growth performance, and survival rate of maanvis fish (Pterophyllumscalare). Keywords: natural and artificial feed; Growth; Survival rate; Maanvis; Pterophyllumscalare